Penerapan Sanksi untuk Meningkatkan Karakter Sportivitas dan Kerjasama pada Pembelajaran Sepakbola - Enang Kuncoro; Victor Novianto (UM Purwokerto Press, 2022)
This research was motivated by the lack of observational journals on the assessment of sportsmanship and cooperation in the football material of class IX-G students of SMP Negeri 4 Purworejo. The aims of this study are: (1) To improve the character of sportsmanship in class IX-G students of SMP Negeri 4 Purworejo, (2) To improve the character of cooperation in class IX-G students of SMP Negeri 4. This research was conducted at SMP Negeri 4 Purworejo with 32 students as research subjects. The object of this research is the character of sportsmanship and cooperation through the provision of sanctions on football material. The instruments used in this study were sportsmanship questionnaires and cooperation questionnaires. The results showed that efforts to improve the character of sportsmanship and cooperation through the provision of sanctions in the form of (1) verbal reprimand, (2) light physical punishment. Through the provision of sanctions when learning soccer material, especially to improve the character of sportsmanship and cooperation, this can be seen after research when playing simple football the sporty character has reached 100% while the cooperative character has reached 90%, so that the provision of sanctions can improve the character of sportsmanship and cooperation.